Avaliação sensorial da carne de bovinos terminados em confinamento com adição de óleo de cravo e canela às dietas - Torrecilhas, Juliana Akamine (2016)
Aiming to evaluate the effect of essential oil of clove (Eugenia caryophyllus) and cinnamon (Cinnamonumzeylanicum) in the diet of feedlot finished young bulls in the perception of consumers at the final product (one and seven days of aging) an experiment was conducted using 40 young bulls half-brothers (¹/2 Brown Swyss- ¹/2 Nellore) feedlot finished and supplemented with essential oil in the diet. The diet consisted of 90% concentrate and 10% pellets of sugar cane offered ad libitum. Young bulls were randomly assigned to one of five diets: CON- control, no essential oil, CLO35 - inclusion of 3500 mg of leaf clove; CLO70 inclusion of 7000 mg of leaf clove, CIN35 - inclusion of 3500 mg of leaf cinnamon, and CIN70 - inclusion 7000 mg of essential oil of leaf cinnamon.The addition of clove oil or cinnamon oil did not alter the visual evaluation and consumer purchase acceptance. Sensory analysis (smell, flavor, tenderness and overall acceptability) was not altered by the inclusion of essential oil in the diet. On the other hand the aging time (seven days) increased acceptability of smell, flavor and tenderness attributes of meat. The addition of this oilscan present benefit on cattle productive parameters, with no impact on consumer visual or sensorial acceptance.